Private security and the investigative process - Nemeth, Charles P., 1951- (CRC Press LLC, 2020)
Private Security and the Investigative Process, Fourth Edition is fully updated and continues to provide complete coverage of the investigative process for private investigations by both individuals and in corporate security environments. This edition covers emerging technology, revised legal and practical considerations for conducting interviews, and new information on case evaluation. Written by a recognized expert in security, criminal justice, ethics, and the law--with over three decades of experience--the updated edition of this popular text covers concepts and techniques that can be applied to a variety of investigations including fraud, insurance, private, and criminal. It details the collection and preservation of evidence, the handling of witnesses, surveillance techniques, background investigations, and report writing. The book reflects best practices and includes tips for ensuring accurate and reliable private sector security investigations. This new edition includes: A new section on career opportunities in paths in the investigative field A rundown of the leading security Industry associations and professional standards being published Added discussion of observational interviews include current protocols analyzing data Details of the current legal implications for security surveillance and practices Advances in technology to thwart crime and fraud in retail and other business settings An entirely new section on e-records from criminal and civil judgments Authoritative, yet accessible, this book is one of the only textbooks dedicated to the subject. It also serves as an important reference for private investigators and security professionals. Complete with numerous forms, checklists, and web exercises, it provides the tools and understanding required to conduct investigations that are professional, ethical, and effective.